Pengaruh TQM terhadap Kinerja Manajerial dengan Motivasi Kerja sebagai Variabel Moderasi - Ridha Risngandika Irawan (Jurnal Bisnis dan Ekonomi, 2019)
This study aims to analyze the effect of TQM on managerial performance and work motivation as a moderating variable. The data used in this study are primary data obtained directly from respondents. Data collection uses a questionnaire distributed to sample members, namely operational managers or parts of production in manufacturing companies in the cities of Seamarang, Ungaran, Salatiga and Solo with the observation year 2019. Samples obtained were 32 respondents per company. Measurement of variables in this study using a Likert scale. Data analysis used is multiple linear regression analysis. Testing the research using SPSS version 16. The results of this study state that TQM does not have a positive effect on managerial performance and work motivation as a moderating variable that cannot moderate the influence of TQM on managerial performance.